A simple preparative method for isolation and purification of polysaccharides from mulberry (Morus alba L.) leaves. (31st January 2013) - Jia, Dongdong; Zhang, Jun; Lan, Rong; Yang, Hongling; Sun, Yongyue
Summary An effective method for preparative extraction and purification of the polysaccharides from mulberry leaves was studied. Orthogonal experiment was carried out to get the optimal conditions (T = 70 °C, pH = 6, t = 60 min, D = 0.4 g g−1 material) of activated carbon decolorisation. The staged, isocratic and multiple ethanol precipitation procedures were also investigated. Through the activated carbon decolorisation and 20% ethanol precipitation procedure, the polysaccharides yield reached 2.91%, and the content of neutral sugar and uronic acid were improved to 21.87% and 57.43% respectively. This process was superior to the macroporous resin adsorption and gel permeation chromatography (GPC) methods. The structure analysis indicated that the purified mulberry leaves polysaccharide (MLP) was composed of Man, GalA and Rha in the ratio of 1.0:7.2:20.0. The molecular weight measured using GPC was approximately 557 062 D. The IR and 1H NMR spectra indicated that the MLP was mainly pectin, which was classified as high‐methoxyl pectin.